Crowdfunding, Efficiency, and Inequality - Hans Peter Grüner; Christoph Siemroth (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
We show how decentralized individual investments can efficiently allocate capital to innovating firms via equity crowdfunding. We develop a model where consumers have privately known consumption preferences and may act as investors. Consumers identify worthwhile investments based on their own preferences and invest in firms whose product they like. An efficient capital allocation is achieved if all groups of consumers have enough wealth to invest.
Keywords: D82; D53; D24; 330